ANALYSIS OF BRAKING DYNAMICS USING LINEARIZED QUARTER VEHICLE MODEL - rozaqi, latif; Rijanto, Estiko (LIPI Press, 2015)
A deep understanding in dynamical characteristics of braking systems is very important in designing an appropriate control system to be applied in a vehicle. This paper examines the braking system dynamics of a car using Quarter Vehicle Model (QVM). In order to facilitate the analysis, a linear model has been derived from a nonlinear QVM. The dynamical characteristics of braking are analyzed using state space equation and then explored through numerical simulation. The result is then compared with nonlinear Euler and 4th order Runge-Kutta methods. In the numerical simulation, the dynamic model is given some different braking inputs and different road conditions to notice the dynamical response of the model. This study learns that applying a sudden braking torque will cause the slip response to move to locked condition too fast. By reducing the input gradient by 48.6673%, 14.3875% improvement on longitudinal speed deceleration will be gained. Therefore, applying braking torque gradually will increase braking effectivity. Moreover, dry asphalt gives the best response compared to both dry concrete and wet asphalt because it gives 9.1940% more effective longitudinal speed deceleration.